2023
DOI: 10.3758/s13423-022-02240-8
|View full text |Cite
|
Sign up to set email alerts
|

An interpretable measure of semantic similarity for predicting eye movements in reading

Abstract: Predictions about upcoming content play an important role during language comprehension and processing. Semantic similarity as a metric has been used to predict how words are processed in context in language comprehension and processing tasks. This study proposes a novel, dynamic approach for computing contextual semantic similarity, evaluates the extent to which the semantic similarity measures computed using this approach can predict fixation durations in reading tasks recorded in a corpus of eye-tracking da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…The current study’s second contribution highlights the usefulness of computational metrics in predicting language processing and comprehension across multiple languages, not only English. Our findings support previous research that demonstrates the predictability of contextual semantic relevance in eye movements during reading and comprehension (e.g., Roland et al, 2012; Frank and Willems, 2017; Sun et al, 2023a). We also found that surprisal effects were present in multiple language processing, which actually supports numerous studies using surprisal to predict language processing (Hale et al, 2022; Hale, 2016; Schrimpf et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study’s second contribution highlights the usefulness of computational metrics in predicting language processing and comprehension across multiple languages, not only English. Our findings support previous research that demonstrates the predictability of contextual semantic relevance in eye movements during reading and comprehension (e.g., Roland et al, 2012; Frank and Willems, 2017; Sun et al, 2023a). We also found that surprisal effects were present in multiple language processing, which actually supports numerous studies using surprisal to predict language processing (Hale et al, 2022; Hale, 2016; Schrimpf et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, contextual semantic information can be linked with short-term memory, a notion supported by empirical investigations into memory systems like the visuospatial sketchpad and phonological loop (Baddeley, 2000;Postle, 2006;Baddeley, 2010). More holistic methods for computing contextual semantic relevance have been proposed (Sun et al, 2023a;Sun et al, 2023b;Sun, 2023). However, in terms of human forgetting mechanism (Murre and Dros, 2015), the current study proposes a method to compute contextual semantic relevance by considering the weights which are determined by the position distance between the target word and its surrounding words (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, such approaches may be improved in terms of comprehensiveness in the types of neighboring words considered and/or the linguistic interpretability of the semantic similarity values obtained. Sun et al (2023a) proposed a dynamic approach for computing contextual semantic similarity, which is cognitively and linguistically interpretable. Meanwhile, Sun et al (2023a) modified the cosine (Frank and Willems, 2017) and Euclidean methods (Broderick et al, 2019), and enabled them more interpretable and effective.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al (2023a) proposed a dynamic approach for computing contextual semantic similarity, which is cognitively and linguistically interpretable. Meanwhile, Sun et al (2023a) modified the cosine (Frank and Willems, 2017) and Euclidean methods (Broderick et al, 2019), and enabled them more interpretable and effective. However, the method of Sun et al (2023a) ignored the different contribution of contextual words and the expectation effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation